Peroxidase Activity in Poplar Inoculated with Compatible and Incompetent Isolates of Paxillus involutus - ABDUL GAFUR; NDRES SCHUTZENDUBEL; ANDREA POLLE (Bogor Agricultural University, Indonesia, 2007)
Peroxidase activity of the hybrid poplar Populus x canescens (Ait.) Sm. (= P. tremula L. x P. alba L.) inoculated with compatible and incompetent isolates of Paxillus involutus (Batsch) Fr. was investigated. Screening of the ectomycorrhizal fungal isolates was initiated with exploration of mycelial growth characteristics and mycorrhizal ability in vitro with poplar. Both traits varied within the fungus although they did not seem to be genetically correlated. While isolates SCO1, NAU, and 031 grew faster than others, only isolates MAJ, SCO1, and 031 were able to form ectomycorrhiza with poplar. Isolates MAJ (compatible) and NAU (incompetent) were subsequently selected for further experiments. Activity of peroxidase, one of the defense-related enzymes, was examined in pure culture and short root components of compatible and incompetent interactions between poplar and P. involutus. Peroxidase activities increased significantly in poplar inoculated with incompetent isolate of the fungus compared to control, while induction of the same enzyme was not detected in compatible associations. Key words: ectomycorrhiza, Paxillus involutus, peroxidase, plant defense, poplar